Utilizing Public Health Frameworks and Partnerships to Ensure Equity in DNA-Based Population Screening - Azriel, Elyse; Henley, Candace; Ehrhardt, Joan; Hampel, Heather; Newlin, Anna; Ramos, Erica; Wicklund, Catherine; Duquette, Debra (Frontiers in Genetics, 2022)
DNA-Based Population Screening in the United States has the promise to improve the health of all people in all communities. We highlight recent DNA-based population screening examples at the state and local level. Key public health principles and concepts with a focus on equity appear to be lacking in current efforts. We request ‘A Call to Action’ that involves all stakeholders in DNA-based population screening. Potential actions to consider include: a) creation of a national multidisciplinary advisory committee with representation from underserved communities; b) utilization of well-described public health screening principles and frameworks (such as Wilson & Jungner) to guide screening decisions and initiatives; c) inclusion of the updated Ten Essential Public Health Services with an equity core in efforts at the local, state and national level; and, d) identification and elimination of systemic barriers that result in health inequities in DNA-based population screening and follow-up.